1997
DOI: 10.1001/archsurg.1997.01430270036006
|View full text |Cite
|
Sign up to set email alerts
|

Does Reoperation for Abdominal Sepsis Enhance the Inflammatory Host Response?

Abstract: Reoperation for abdominal sepsis frequently causes substantial hypotension, and is, thus, potentially harmful to the patient. Reoperative trauma may induce an early postoperative increase in interleukin-6 levels. Because this increase occurs before the development of hypotension, a relationship between the kinetics of this cytokine and the observed hemodynamic instability may be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 36 publications
1
20
0
4
Order By: Relevance
“…> Bei adäquater Fokussanierung und gründlicher Lavage reicht in ca. 90% eine einzige Operation aus Sautner und Kollegen konnten nachweisen, dass geplante Relaparotomien durch die systemische Entzündungsant-wort schädlich sein können [6,23]. Zudem steigt die Rate lokaler und systemischer Komplikationen mit der Anzahl geplanter Relaparotomien an [13].…”
Section: Prävention Persistierende/ Rezidivierende Entzündungunclassified
“…> Bei adäquater Fokussanierung und gründlicher Lavage reicht in ca. 90% eine einzige Operation aus Sautner und Kollegen konnten nachweisen, dass geplante Relaparotomien durch die systemische Entzündungsant-wort schädlich sein können [6,23]. Zudem steigt die Rate lokaler und systemischer Komplikationen mit der Anzahl geplanter Relaparotomien an [13].…”
Section: Prävention Persistierende/ Rezidivierende Entzündungunclassified
“…[2][3][4] However, repeated or even unnecessary surgical procedures are an additional risk factor for the patient and may further enhance morbidity. [5][6][7] Facing this clinical dilemma, there is major interest in the search for an optimum diagnostic tool for an early, noninvasive, and reliable diagnosis of abdominal infections and sepsis. 8 Clinical scoring systems allow satisfactory prediction of overall prognosis [9][10][11][12][13][14] and are an established means of interinstitutional comparison of patient groups for study purposes.…”
mentioning
confidence: 99%
“…In some studies, high mortality rates have been reported following UARLs performed due to peritonitis. On the other hand, there are studies reporting reduced mortality rates following planned re-laparatomies since they provided effective irrigation and drainage (11)(12)(13)(14). Consideration of UARLs has been suggested in the treatment of uncontrolled intra-abdominal infection and multisystem organ failure (15).…”
Section: Discussionmentioning
confidence: 99%
“…Despite multi-redolaparatomies performed on the patients, high mortality rates were encountered. In the study of Sautner T et al, re-laparatomies performed on patients with abdominal sepsis were reported to increase the inflammatory response, and the increased inflammatory response was reported to increase the mortality rates (12). In another study, re-laparatomy was reported to change the multi-system organ failure into an irreversible situation when the treatment to be performed with re-laparatomy was not properly selected (16).…”
Section: Discussionmentioning
confidence: 99%